Complementary medicine practitioner consultations amongst 1, 314 individuals with chronic conditions: Characteristics of users, reasons for and predictors of use. (August 2020) - Foley, Hope; Steel, Amie; McIntyre, Erica; Harnett, Joanna; Sibbritt, David; Wardle, Jon; Adams, Jon
Abstract: Background: The complexity of chronic conditions challenges health systems and patients. Patients with chronic conditions often consult complementary medicine (CM) practitioners. Optimal care of chronic conditions requires understanding of the characteristics and consultation behaviours of these patients. Methods: Cross-sectional survey (n = 2025 adults), broadly representative of the Australian population. Measures included sociodemographics, health status and health service utilisation. Data from participants with chronic conditions were analysed. Results: Of the 1314 participants reporting chronic conditions, 38.4% consulted a CM practitioner. Significant differences were observed between participants who did/did not consult CM practitioners, across all sociodemographics and some health status items. The most reported reason for consultation was to support wellbeing. Predictors of consultation were younger age, employment, and private health insurance coverage for CM, however, predictors varied by profession consulted. Conclusion: CM consultations amongst those with chronic conditions appear to be influenced by sociodemographic and economic factors, and quality of life needs. Highlights: Patients with chronic conditions consult CM practitioners to improve wellbeing. Socioeconomic determinants of health appear to influence use of CM practitioners. CM practitioners may be utilised during chronic illness to address quality of life.